PENINGKATAN KAPASITAS KELOMPOK TANI HUTAN GOLLANA SANGTANDUNG DALAM PENGOLAHAN NIRA AREN MENJADI GULA SEMUT (GULA GRANULAR ) - Witno Witno; Yumna Yumna; Dewi Marwati Nuryanti; Maria Maria (Universitas Mataram, 2022)
One of the products that can be created from the micro industry is processing palm sap into granulated sugar, commonly known as ant sugar. In the forestry sector, sugar palm is one of the plants included in the category of Non-Timber Forest Products. NTFPs are non-timber forest products that have economic value and benefit many people. This activity aims to determine the capacity of forest farmer groups in processing palm sap into palm sugar using modern technology in the form of crystallite and sorting machines. The methods used are socialization, counselling and using tools for the product packaging. The result of this activity is that public knowledge regarding processing palm sugar using modern technology is still lacking and not used to it. After practising the use of tools accompanied by a team and technicians, community knowledge of the use of modern technology tools in the form of Crystallator and Sorting machines also increased from not knowing to know. Likewise, in terms of product packaging, people who initially used ordinary tools and even used leaves have now expanded to tofu and can use modern packaging tools. However, it is necessary to provide continuous assistance. This activity concludes that the community has been able to use modern tools and package products properly even though they still need help for marketing and stock.